Lithostratigraphy of the Tecocoyunca Group (Middle Jurassic) in the Ñumi River Area (vicinity of Tlaxiaco), Oaxaca, and considerations about the regional distribution of the biota - Raúl, Carrasco-Ramírez S. (2016)
The Jurassic lithostratigraphy of the Mixteca Region is relatively well known, however the system on which is based includes formational descriptions somewhat deficient (e.g. vagueness, characterization by fossil content, insufficient cartographic discrimination). In order to contribute to correct such deficiency, we undertook a detailed study of the Río Ñumí area, vicinity of Tlaxiaco, where the Middle Jurassic units that make up the Tecocoyunca Group display their attributes, thus allowing to supplement the formational descriptions. It was found that locally, the Tecocoyunca Group includes in the lower part the associated Formations Zorrillo/Taberna (Early to Late Bajocian), consisting of ~287 m of carbonaceous siltstone, mudstone and subarkosic very fine-grained sandstone and siltstone; this composite unit bears pelecypods and continental plants, as well as two carbon zones; it is interpreted that they were part of a delta complex. These associated formations conformably underlie the Simon Formation (Middle-Late Bathonian), it consists of ~270 m of subarkoses and siltstone set in thin to thick strata; it is interpreted as a transitional deposit. This unit concordantly underlies the Otatera Formation (Late Bathonian), consisting of ~170 m of pelecypod coquina with intercalations of spathitic limestone strata; it is regarded as shallow neritic deposit with a subordinate beach component. This unit concordantly underlies the Yucuñuti Formation (Middle Callovian), constituted by ~118 m of fine-grained sandstone, coquina and biomicrite that bear pelecypods and gastropods; it is interpreted as a transitional to shallow neritic deposit. This unit is unconformably overlain the Oxfordian Limestone with “Cidaris,” which is no part of this group. The Tecocoyunca Group Biota includes a typical Middle Jurassic flora, whose taxa are widely distributed in Mexico’s central and southern regions, as well as in northern Central America; and a paleofauna constituted by Middle Jurassic mollusks common throughout the Mixteca Region. The biota as a whole discloses a warm and humid climate regime. Finally, it is thought that the detailed descriptions of the formations making up the Tecocoyunca Group are in fact an advance in the redefinition of the Mixtec Region’s Middle Jurassic units.